S-cone circuits in the primate retina for non-image-forming vision. (June 2022) - Patterson, Sara S.; Neitz, Maureen; Neitz, Jay
Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) respond directly to light by virtue of containing melanopsin which peaks at about 483 nm. However, in primates, ipRGCs also receive color opponent inputs from short-wavelength-sensitive (S) cone circuits that are well-suited to encode circadian changes in the color of the sky that accompany the rising and setting sun. Here, we review the retinal circuits that endow primate ipRGCs with the cone-opponency capable of encoding the color of the sky and contributing to the wide-ranging effects of short-wavelength light on ipRGC-mediated non-image-forming visual function in humans.